Il calcio come esperienza formativa… a due facce - Cambi, Franco (Studi sulla Formazione/Open Journal of Education, 2023)
Football is both an educational experience for those who play it and for those who follow it, then it is also a mass myth and an activity increasingly governed by the market. So football today has a complex face. But there, more and more, team play must become the rule, with its ethical, mental and, indeed, educational values.